Ligand-sensitized lanthanide(III) luminescence with octadentate bispidines - Braun, Felix; Comba, Peter; Herten, Dirk-Peter; Pokrandt, Bianca; Wadepohl, Hubert (Inorganica chimica acta, 2019)
The octadentate bispidine ligand L (bispidine=3,7-diazabicyclo[3,3,1]nonane) with two pyridine groups at C2 and C4 and two picolinates at N3 and N7, providing two tertiary amines, four pyridines and two carboxylates to metal ions, has been coordinated to lanthanide(III) ions (SmIII, EuIII, TbIII, DyIII, HoIII). The single crystal X-ray structures of [TbIII(L)(NO3)] and [HoIII(L)(OH2)](TFA) (TFA=trifluoracetate) have been determined and define the complexes as 9-coordinate with a monodentate nitrate or a water molecule completing the coordination sphere. Spectroscopy indicates that in solution all complexes are 9-coordinate with an OH2 coordinated to the lanthanide(III) center. Absorption and emission spectra show that the ligands function as antennas with UV excitation (260nm) leading to relatively high intensity emission in the visible region (500-600nm) with millisecond lifetimes of the excited states.